2015
DOI: 10.18632/oncotarget.3184
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation by microRNA-200b-3p and microRNA-200b-5p in the inhibition of epithelial-to-mesenchymal transition in triple-negative breast cancer

Abstract: Epithelial to mesenchymal transition (EMT) involves loss of an epithelial phenotype and activation of a mesenchymal one. Enhanced expression of genes associated with a mesenchymal transition includes ZEB1/2, TWIST, and FOXC1. miRNAs are known regulators of gene expression and altered miRNA expression is known to enhance EMT in breast cancer. Here we demonstrate that the tumor suppressive miRNA family, miR-200, is not expressed in triple negative breast cancer (TNBC) cell lines and that miR-200b-3p over-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 72 publications
(62 reference statements)
6
62
1
Order By: Relevance
“…In the MDA-MB-435 cell line, the invasive cell number decreased to 15.2% in chitosan/miR200c group accordingly to untreated tumor group (p b 0.05). After the re-upregulation of miR-200c by using chitosan nanoplexes, the breast cancer cell invasion diminished according to our findings, which was similar to earlier data (Pecot et al, 2013;Rhodes et al, 2015). Ulhmann et al (2010) and Humphries and Yang (2015) reported the reducing effect of the miR-200c family on cancer cell intravasion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the MDA-MB-435 cell line, the invasive cell number decreased to 15.2% in chitosan/miR200c group accordingly to untreated tumor group (p b 0.05). After the re-upregulation of miR-200c by using chitosan nanoplexes, the breast cancer cell invasion diminished according to our findings, which was similar to earlier data (Pecot et al, 2013;Rhodes et al, 2015). Ulhmann et al (2010) and Humphries and Yang (2015) reported the reducing effect of the miR-200c family on cancer cell intravasion.…”
Section: Discussionsupporting
confidence: 92%
“…2). This data showed a similarity with previous papers related to the downregulation of miR-200c in cancer cells (Deng et al, 2014;Rhodes et al, 2015). In this study, we tried to increase the miR-200c levels of the cells by transfecting the cancer cells with chitosan nanoplexes containing miR-200c to reach miR-200c level of the normal (healthy) cells (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To gain greater insight into the effects of the miR-335 transcript on estrogen signaling we performed qRT-PCR to determine basal expression levels of pre-miR-335, miR-335-5p, and miR-335-3p across a series of breast cancer cell lines (ERα + and ER − ). miR-335-3p was included in our analysis due to recent evidence suggesting a functional role for both strands of the miRNA duplex [22]. qRT-PCR results demonstrated that both miR-335-5p and miR-335-3p were robustly expressed across all breast cancer cell lines regardless of receptor status, with expression at physiologically relevant levels (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the well-established role of the reduced miR200b-3p expression in EMT and associated oncogenesis, tumour metastasis and invasion,12–17 little are known for miR200b-5p, possibly because it represents the star strand, which is generally considered to degrade during miRNA biogenesis 24. Recently, it has been reported that miR200b-5p controls the non-canonical EMT in synergy with miR200b-3p by targeting PRKCA and PIP4K2A molecules in the RHOGDI pathway 25. Interestingly, miR200b miRNAs have been almost exclusively associated with solid tumours.…”
Section: Discussionmentioning
confidence: 99%